Acoustic and Perceptual Characteristics of Mandarin Speech in Gay and Heterosexual Male Speakers. (December 2022) - Geng, Puyang; Gu, Wentao
This study investigated acoustic and perceptual characteristics of Mandarin speech produced by gay and heterosexual male speakers. Acoustic analysis of monosyllabic words showed significant differences between the two groups in voice fundamental frequency (F0), F1 of low vowel, and duration of aspiration/frication in consonants. The acoustic patterns on F0, formants, and center of gravity as well as spectral skewness of /s/ differed from those reported for Western languages like American English, which could be interpreted from a sociopsychological point of view based on different acceptability of gay identity in the two societies. The results of a perceptual experiment revealed significant but weak correlations between the acoustic parameters and the score of perceived gayness, which was significantly higher on gay speech than on heterosexual male speech. Although the observed F0 and F1 patterns in Mandarin gay speech were opposite to the stereotype of gayness, gay identity can still be identified to some extent from speech due to the existence of other acoustic cues such as a longer fricative duration, which is not a stereotype of gayness but has been consistently observed in Mandarin and Western languages.